Microplastics: A threat to Fetoplacental unit and Reproductive systems - Abass Toba Anifowoshe; Md Noor Akhtar; Abisola Majeed; Asem Sanjit Singh; Toyyibah Funmilayo Ismail; Upendra Nongthomba (Toxicology Reports)
Plastic pollution has become a pressing global environmental and public health challenge, raising significant concerns about its potential effects on human health. While extensive research has been conducted on micro- and nanoplastics (MNPs), there remains a critical gap in understanding how these plastic particles traverse the maternal-fetal interface and contribute to reproductive anomalies. This review aims to address this knowledge gap by examining the effects of MNPs on the fetoplacental unit, a vital structure that serves as the interface between the mother and fetus during pregnancy, as well as on the broader reproductive system. Traditionally viewed as a protective barrier safeguarding the fetus, emerging evidence suggests that the placenta may also act as a site for the accumulation of plastic particles, thereby compromising its function. A literature search was conducted using a combination of keywords on Google Scholar and PubMed including ’plastic particles affect the fetoplacental unit’, ’how plastic particles traverse the maternal-fetal contact’, and reproductive abnormalities induced by micro/nano-plastics’. Key studies show that plastic particles can traverse the maternal-fetal interface, potentially exposing developing fetuses to various harmful chemicals present in plastics, such as endocrine disruptors and persistent organic pollutants. Once in contact with the fetoplacental unit, these particles may trigger inflammatory responses, oxidative stress, and even epigenetic modifications. They also bioaccumulate in testes, altering spermatogenesis, spermatozoa morphology, testosterone production, body weights, and inflammation as reported in mice. Such disruptions can increase the risk of developmental and reproductive disorders in the fetus, suggesting that exposure to plastic particles may carry long-term health implications. Further studies highlight the particular vulnerability of the fetoplacental unit to plastic particles. The placenta has limited detoxifying capabilities and unique immunological regulation, making it especially sensitive to foreign particles. Identifying critical windows of susceptibility during pregnancy is germane, as exposure to plastic particles during these periods could have heightened effects on fetal development. This growing concern underscores the urgent need for comprehensive research into the mechanisms through which plastic particles impact the fetoplacental unit. Additionally, this review calls for stronger measures to mitigate plastic pollution and recommends health strategies aimed at protecting future generations from potential harm. It synthesizes recent findings on the ways in which these particles influence the fetoplacental unit and the broader reproductive system.